PERANCANGAN IDENTITAS VISUAL TOKO SARIHON BAN: Visual Identity Design of Sarihon Ban Tire Shop - Edy Chandra; Naka Nara Nata (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2026)
Visual Identity Design of Sarihon Ban Tire Shop. This study addresses brand image stagnation at Sarihon Ban, a local tire service enterprise operating for over two decades without a professional visual identity. In an increasingly competitive market, visual identity is essential in shaping consumer trust and perceived service quality. The research aims to develop a visual identity system that conveys strong, modern, and trustworthy values while preserving established credibility. A qualitative, design-based research approach was employed, including literature review, questionnaires, interviews, SWOT analysis, and visual exploration. The study resulted in a comprehensive visual identity system comprising a logo, color palette, typography, a Graphic Standards Manual, and multi-media applications. The findings demonstrate that strategically designed visual identity significantly enhances professional image, brand awareness, and competitiveness among automotive service micro, small, and medium enterprises. Furthermore, this research contributes to visual branding studies by highlighting visual identity as a strategic tool influencing pre-service trust and perceived quality, an area that remains underexplored in automotive service MSMEs.